New species of Blaesodactylus (Squamata: Gekkonidae) from Tsingy karstic outcrops in Ankarana National Park, northern Madagascar - Jono, Teppei; Bauer, Aaron M.; Brennan, Ian; Mori, Akira (Zootaxa, 2015)
We describe a new gecko of the genus Blaesodactylus from a karstic outcrop in deciduous dry forest of Ankarana National Park, northern Madagascar. Blaesodactylus microtuberculatus sp. nov., the fifth recognized species of Blaesodactylus, is distinguished from all other congeners, B. ambonihazo, B. antongilensis, B. boivini and B. sakalava by a combination of small, homogeneous gular granules, unspotted venter and lack of tubercles on distal part of original tail. Mitochondrial (ND2 and ND4) and nuclear (RAG-1) DNA identify a consistent divergence between B. microtuberculatus and its allotopic sister species B. boivini. We highlight habitat partitioning in these allotopic congeners where Blaesodactylus microtuberculatus inhabits karstic outcrops in Tsingy massif, and B. boivini dwells on tree trunks in deciduous dry forest.